Green synthesis of TiO2 nanoparticles by using aqueous extract of Jatropha curcas L. latex - Hudlikar, Manish; Joglekar, Shriram; Dhaygude, Mayur; Kodam, Kisan M. (Materials Letters, 2012)
Present study deals with a green synthesis of TiO2 nanoparticles by using 0.3% aqueous extract prepared from latex of Jatropha curcas L. TiO2 nanoparticles were characterized by X-ray diffraction (XRD), Selected Area Electron Diffraction (SAED), Transmission Electron Microscopy (TEM), Energy Dispersive Analysis of X-rays (EDAX) and Fourier Transform Infrared Spectroscopy (FTIR). Fourier Transform Infrared Spectroscopy (FTIR) were performed to find the role of curcain (enzyme), cyclic peptides namely curcacycline A (an octapeptide) and curcacycline B (a nonapeptide) as a possible reducing and capping agents, present in the latex of J. curcas L. The average size of TiO2 nanoparticles was found to be in the range of 25 to 100 nm. Our result shows that there are two broad categories of nanoparticles, first having diameter from 25 to 50 nm which are mostly spherical in shape and second having some larger and uneven shapes. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biomaterials; Electron microscopy; Fourier Transform Infrared Spectroscopy (FTIR); Nanostructures